MICROSURGICAL TREATMENT OF POST-TRAUMATIC INJURIES OF THE BRACHERIC PLEXUS (World Bulletin of Public Health, 2022)
Of all trauma to the nervous system, the proportion of damage to the peripheral nervous system is 6%. Of this number, injuries to the brachial plexus and its branches account for 70%. This topic is relevant, since inadequate treatment of traumatic injuries of the brachial plexus leads to permanent disability. Neurosurgeons, traumatologists, reconstructive and plastic surgeons deal with surgical treatment of brachial plexus injuries. This paper presents the most effective methods of surgical treatment of injuries of the brachial plexus.